Investigating the Interaction of Chitin in Organic Electrolyte Solutions Using Molecular Dynamics - Carroll, Lenard Leslie (Department of Chemistry, 2020)
The dissolution, hydrolysis and fermentation of biopolymers afford biofuels, an alternative source of energy. Unfortunately, biopolymers have hydrogen bonding networks that are difficult to disrupt and dispersion forces to overcome, all of which make it insoluble in most common organic solvents and water under moderate conditions. Much work has been devoted to improving the dissolution of biopolymers, via alternative solvents or by developing new ground-breaking processes. One alternative solvent that has become quite popular in biomass dissolution studies are ionic liquids (ILs). Ionic liquids are attractive solvents due to its broad range of uses and advantageous properties. ILs have been promising in its use in separation, extraction, catalysis, lubricants, fuel cells, batteries and liquid crystal research. ILs also have low vapour pressure, which implies low toxicity with respect to their clean-up. While many ILs are produced under environmentally unfriendly conditions, more studies are being done on finding ways to synthesise these species using the 12 design principles of Green Chemistry. While a plethora of studies has been done on the experimental dissolution of cellulose in ionic liquids, similar studies have been minimal for chitin. As such, a computational investigation on the dissolution of chitin in ionic liquids and organic electrolyte solutions (OESs) is presented here. OESs consists of an ionic liquid and an additional aprotic organic molecular solvent, known henceforth as a co-solvent. These mixtures are considered as some ILs have high viscosities, which decreases its ability to effectively dissolve biopolymers, but by adding co-solvents to the IL, the mixture’s viscosity decreases, potentially improving on the solubility of the biopolymer. Computationally, the dissolution of chitin was modelled through molecular dynamics simulations as implemented in the AMBER MD code, by studying the separation of two 4-methyl-β-D-Nacetylglucosamine-(1→4’)-1’-methyl-β-D-N’-acetylglucosamine ((GlcNAc)2Me2) molecules (chosen as the model for chitin) in various solvent systems using potential of mean force calculations. The ionic liquids of choice were 1-butyl-3-methylimidazolium acetate ([C4C1im][CH3COO]) and 1-butyl3-methylimidazolium methyl sulfate ([C4C1im][CH3SO4]), two ILs that have experimental physical properties available, a requirement for MD simulation validation. The co-solvents chosen were dimethyl carbonate, propylene carbonate and γ-valerolactone, three structurally similar bio-based solvents. The solvation of a (GlcNAc)2Me2 monomer was also studied in this project via radial distribution functions, interaction energies and hydrogen bond analyses, as to support the results produced from the separation study. Additionally, the experimental swelling of chitin was investigated as to compare it to the interaction energy results, acting as further validation of the computational results. The computational results suggest that the (GlcNAc)2Me2 monomer will interact more favourably with pure [C4C1im][CH3COO], followed by the 8:2 [C4C1im][CH3COO]:co-solvent OESs, the 2:8 [C4C1im][CH3COO]:co-solvent OESs and then the pure co-solvents. The solvation study agrees with this trend. The PMF results also show that a (GlcNAc)2Me2 dimer will separate spontaneously in all the solvent systems, with the least amount of thermodynamic work required (to separate) in pure [C4C1im][CH3COO], and the most in pure dimethyl carbonate.